Comparing Perceptions of Different E - Advertising Formats - Singh, Seema; Ahlluwalia, Sarika (Indian Journal of Marketing, 2017)
Ever since the Hot Wired sold its first banner ad to AT&T Corp. in 1994, e-advertising is continuously evolving. With the availability of increased bandwidth and advanced technologies, more sophisticated e-advertising formats are available. For effective advertising, it is important to understand how consumers perceive different e-advertising formats. Previous studies have confirmed that consumers have significantly different perceptions across formats. The present study investigated consumers’ perception of six e-advertising formats (banner ads, pop-ups, keyword search, sponsorships, interstitials, e-mail) in terms of five perceptual measures (information value, entertainment value, trustworthiness, offensiveness, and effect on product price). It was found that consumers’ perceptions across e-advertising formats were different and each e-advertising format was perceived differently on each perceptual measure under study.